2017
DOI: 10.21608/ejnf.2017.75210
|View full text |Cite
|
Sign up to set email alerts
|

Use of Feed Color and Odor as Attractive Tools for Managing Turkey Chicks at Early Feeding

Abstract: total number of 180 one-day old unsexed native turkey chicks were chosen for evaluating the response of turkeys to different feed odors and colors on growth performance, carcass characteristics, some meat quality and health traits. Birds were allocated in three main groups according to feed odor (non-odor, molasses and fish odors) and then each main group was divided to two subgroups corresponded to non-colored and green colored feed, respectively. The findings indicated that birds fed diets of molasses or fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The reason could be that the colour of the feed attracts chicks, causing them to feed early, which improves the development of their digestive and immune systems. The results were in agreement with [12] and [7], [13] while these results differed with [3] that there were no significant differences between the treatments.…”
Section: Growth Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…The reason could be that the colour of the feed attracts chicks, causing them to feed early, which improves the development of their digestive and immune systems. The results were in agreement with [12] and [7], [13] while these results differed with [3] that there were no significant differences between the treatments.…”
Section: Growth Parameterssupporting
confidence: 86%
“…The reason may be due to the use of coloured fodder in the early days of the birds' lives, where some of the fodder colours are attractive to the newly hatched chick, which helps them to find feed early, or the attraction of birds to the green colour may be due to the colours of [14]. Promote weight gain [15].…”
Section: Growth Parametersmentioning
confidence: 99%
“…Birds fed diets contained molasses and fresh fish meat significantly (P 0.05) increased body weight gains compared with that obtained from birds either fed diets contained skim milk or fresh whole egg. Farghly (2017) and Farghly and Abou-Kassem (2014) observed that final body weight and body weight gain of birds fed green and red significantly (P≤0.05) increased than those of non colored feed group. However, in contrast to these findings Farghly and Sharara (2016) found that colored feed insignificantly affected body weight performance in local turkey.…”
Section: Body Weight and Gainmentioning
confidence: 94%
“…It was concluded that the local turkey prefer green feed as well as green feeders over orange, yellow, red feeders and white, orange, yellow or red feeds, respectively. Farghly and Mahrose (2017) and Farghly (2017) found that turkey poults fed green feed were insignificantly higher in their BW than the other groups and that was reflected on the marketing weight. While, they showed insignificant differences in FC and FCR of the experimental groups due to feed color.…”
Section: Feed Consumption and Conversionmentioning
confidence: 97%
See 1 more Smart Citation